Is it all That Bad When Living with an Intracellular Protozoan? The Role of Trypanosoma cruzi Calreticulin in Angiogenesis and Tumor Growth - Ramírez-Toloza, Galia; Aguilar-Guzmán, Lorena; Valck, Carolina; Abello, Paula; Ferreira, Arturo (Frontiers in Oncology, 2015)
The immune system protects against disease, but may aberrantly silence immunity against “altered self”, with consequent development of malignancies. Among the components of the endoplasmic reticulum (ER), important in immunity, is calreticulin (CRT) that, in spite of its residence in the ER, can be translocated to the exterior. Trypanosoma cruzi is the agent of Chagas disease, one of the most important global neglected infections, affecting several hundred thousand people. The syndrome, mainly digestive and circulatory, affects only one third of those infected. The antitumor effects of the infection are known for several decades; but advances in the identification of responsible T. cruzi molecules are scarce. We have shown that T. cruzi CRT (TcCRT), better executes the antiangiogenic and antitumor effects of mammal CRT and its N-terminus vasostatin. In this regard, rTcCRT and/or its N-terminus inhibit angiogenesis in vitro, ex vivo and in vivo. On the other hand, rTcCRT inhibits the growth of murine adenocarcinomas and melanomas. Finally, rTcCRT fully reproduces the antitumor effect of T. cruzi infection in mice. Thus we hypothesize that, the long reported antitumor effect of T. cruzi infection, is mediated at least in important part by TcCRT.